1974
DOI: 10.1128/aac.5.5.534
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Plasmid Determining Resistance to Erythromycin, Lincomycin, and Vernamycin B α in a Strain of Streptococcus pyogenes

Abstract: A plasmid determining resistance to erythromycin, lincomycin, and vernamycin Ba was isolated from a strain of Streptococcus pyogenes. The plasmid has a molecular weight of approximately 17 x 108 and is present to the extent of one to two copies per chromosomal genome equivalent.Erythromycin and lincomycin are antibiotics used in the treatment of group A beta-hemolytic streptococcus (Streptococcus pyogenes) infections in patients for whom penicillin is contraindicated. S. pyogenes strains are usually susceptibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
48
0

Year Published

1975
1975
2011
2011

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 99 publications
(51 citation statements)
references
References 13 publications
3
48
0
Order By: Relevance
“…In several cases, the molecular masses of these plasmids are similar, with plasmid DNA being of a size of approximately 17 megadaltons (6,9,13,26). In one case we showed that plasmid pAM,8l from S. faecalis strain DS-5 was approximately 95% homologous with a plasmid of similar size in S. pyogenes strain AC-1 (36 …”
mentioning
confidence: 80%
See 1 more Smart Citation
“…In several cases, the molecular masses of these plasmids are similar, with plasmid DNA being of a size of approximately 17 megadaltons (6,9,13,26). In one case we showed that plasmid pAM,8l from S. faecalis strain DS-5 was approximately 95% homologous with a plasmid of similar size in S. pyogenes strain AC-1 (36 …”
mentioning
confidence: 80%
“…pyogenes (6,25,28), and a group B streptococcus (20). In several cases, the molecular masses of these plasmids are similar, with plasmid DNA being of a size of approximately 17 megadaltons (6,9,13,26).…”
mentioning
confidence: 84%
“…Resistance to this antibiotic in Escherichia coli has been found to be due to alterations in either of the ribosomal proteins L4 or L22 (Gale et al, 1981) and, more recently, to enzymic hydrolysis of the antibiotic (Barthelemy ut al., 1984). In clinical isolates of Staphylococcus aureus (Lai & Weisblum, 1971) and of Streptococcus pyogenes (Clewell & Franke, 1974), a relationship has been demonstrated between resistance to erythromycin and a characteristic pattern of coresistance to other macrolides, lincosamides and B-type streptogramins, which was termed the MLS-phenotype. This phenotype has been shown to depend on the presence of N6-dimethyladenine in 23s ribosomal RNA (Lai et al, 1973).…”
Section: Introductionmentioning
confidence: 99%
“…31 Another undergraduate student, Art Franke identified an erythromycin resistance plasmid in Streptococcus pyogenes, an important human pathogen. 32 And we eventually found plasmids also in Streptococcus faecalis 33 and S. sanguis. 34 As discussed below there was much to get excited about regarding where some of these new findings would take us, and within a few years our work with ColE1 came to an end.…”
Section: New Territorymentioning
confidence: 99%